Apology and non-apology strategies in the EFL context of Iranian Azerbaijani pre-university students / Haleh Parsa - Haleh , Parsa (2018)
The aim of this study was to explore apology and non-apology strategies of Iranian Azerbaijani EFL pre-university students in EFL. Data were collected from 100 participants (50 males, 50 females) studying at advanced level of English ranging between 16 and 18 years of age. The research design was a qualitative method and an open questionnaire namely Discourse Completion Test (DCT), role play, and interview were used to triangulate the data. The variables under study were gender, social distance, and social dominance (power). The data collected through the methods were examined for statistical figures based on Cohen and Olshtain (1981) and Olshtain and Cohen (1983) frameworks. The results revealed that Iranian Azerbaijani EFL students were explicit in their apologies and intensified them to enrich the realization of apology act. Like two context-external variables namely social distance and social dominance (power), gender was a significant factor and there was an influence of Azerbaijani language (L1) on Iranian Azerbaijani EFL pre-university students’ use of apologies. Although explicit, intensified and polite strategies were offered to strangers, less formal and non-apology strategies were used to close friends. Besides, IFIDs, apology, and fewer non-apologies were applied to people of higher social status.